Sacred Text Narratives and Religious Violence: The Case of Islamic Defenders Front (FPI) in Indonesia - Hikmatul Akbar; Noorhaidi Hasan; Dicky Sofjan (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2023)
FPI is one among several Islamist Groups in Indonesia. Seeing through its fierce actions, people tend to judge FPI as radicals. Some political elites even classify it as terrorist. Despite the fact that it violates many rules, FPI claims to be a religious and pious one. The government disbanded FPI at the end of 2020 because of its numerous violent actions. However, it continues to get support from many Islamic communities. For some conservative Muslims, FPI actions are a sample of how Islamic teaching should be applied in daily life. Using qualitative research and narrative analysis, this paper explored the narrative of Sacred Text, especially the Quran and Hadith presented by FPI, on how it is managed, interpreted, and spread to the public. This paper also explored the possible errors FPI made in narrating sacred text. The results show FPI’s determination to interpret and narrate sacred text as a way to achieve a goal, without considering the views of other religious scholars and books that can better guide narrating and interpreting the Sacred Text.